2017
DOI: 10.3389/fpls.2017.00204
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Genome Analysis of Resurrection Tertiary Relict Haberlea rhodopensis Highlights Genes Important for Desiccation Stress Response

Abstract: Haberlea rhodopensis is a paleolithic tertiary relict species, best known as a resurrection plant with remarkable tolerance to desiccation. When exposed to severe drought stress, H. rhodopensis shows an ability to maintain the structural integrity of its photosynthetic apparatus, which re-activates easily upon rehydration. We present here the results from the assembly and annotation of the chloroplast (cp) genome of H. rhodopensis, which was further subjected to comparative analysis with the cp genomes of clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 75 publications
7
83
0
Order By: Relevance
“…Among the ten most divergent coding regions in this study, matK has been considered as core universal DNA barcodes in many species (Li et al 2019), and ycf1 has recently been widely applied in plant phylogeny and DNA barcoding studies (Dong et al 2015;Yang et al 2017). Besides, accD, rps19, ccsA and ndhF have also been proved to exhibit large divergence among various plant lineages and can be applied in phylogenetic studies (Ni et al 2016;Ivanova et al 2017). The boundaries of IRs and LSC/SSC differs among various plant species (Nie et al 2012;Ni et al 2016;Yan et al 2019;Li et al 2019), and expansion/extraction of the IR regions often lead to size variation of chloroplast genomes (Wang et al 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Among the ten most divergent coding regions in this study, matK has been considered as core universal DNA barcodes in many species (Li et al 2019), and ycf1 has recently been widely applied in plant phylogeny and DNA barcoding studies (Dong et al 2015;Yang et al 2017). Besides, accD, rps19, ccsA and ndhF have also been proved to exhibit large divergence among various plant lineages and can be applied in phylogenetic studies (Ni et al 2016;Ivanova et al 2017). The boundaries of IRs and LSC/SSC differs among various plant species (Nie et al 2012;Ni et al 2016;Yan et al 2019;Li et al 2019), and expansion/extraction of the IR regions often lead to size variation of chloroplast genomes (Wang et al 2008).…”
Section: Discussionmentioning
confidence: 93%
“…We speculate that relaxed neutral selection (Ka/Ks value around 1.0) and potential positive selection (Ka/Ks value greater than 1.0) of rpl23 , rpl36 , and rps7 in various species here reflects the highly diverse environments and adaptions of plants (Table S4). For gene ycf1 , it is one of the largest genes in chloroplast genome and usually has two functional copies [22,25], or one of the two copies was evolved to be a pseudogene in some plants [19,3133] as well as in 11 mangroves ( Avicennia marina , Xylocarpus moluccensis , Hibiscus tiliaceus , Excoecaria agallocha , Bruguiera sexangula , Kandelia obovata , Rhizophora stylosa , Ceriops tagal , Sonneratia ovata , Pemphis acidula , Laguncularia racemose ). In this study, most species in Malpighiales including one mangrove Excoecaria agallocha , have ycf1 Ka/Ks values around or greater than 1.0, while about 0.4 in Malvales, Myrtales and Sapindales, and about 0.6 in Fabales and Lamiales, showing the diverse evolve rates in different species (Table S4, Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The RSCU values represented synonymous codon bias with a high proportion of A or T at the third position, similar to the cp genomes of other angiosperms [28][29][30]. The amino acid of high RSCU values infers that the contribution functionally prevents error in the peptide or transcription process [28,30]. Overall, the characterization of three Actaea cp genomes showed that these genomes are highly conserved, similar to the cp genomes of other Actaea species [10,11].…”
Section: Features Of the Cp Genomes Of Three Actaea Speciesmentioning
confidence: 57%
“…The value of relative synonymous codon usage (RSCU) was greater than 5 for arginine (Arg), Leu and Ser, as expected ( Figure S2B). The RSCU values represented synonymous codon bias with a high proportion of A or T at the third position, similar to the cp genomes of other angiosperms [28][29][30]. The amino acid of high RSCU values infers that the contribution functionally prevents error in the peptide or transcription process [28,30].…”
Section: Features Of the Cp Genomes Of Three Actaea Speciesmentioning
confidence: 63%